Roux-en-Y gastric bypass potentially improved intestinal permeability by regulating gut innate immunity in diet-induced obese mice - Zhangliu Jin (Nature Portfolio, 2021)
Abstract Roux-en-Y gastric bypass (RYGB) has been demonstrated to be the most effective treatment for morbid obesity, yet the impact of RYGB on intestinal permeability is not fully known. In this work, we subjected obese mice to RYGB and sham operation procedures. Serum lipopolysaccharide (LPS) level, inflammatory cytokines and intestinal permeability were measured at 8 weeks post surgery. In contrast to sham surgery, RYGB reduced body weight, improved glucose tolerance and insulin resistance, and decreased serum levels of LPS, IL6 and TNFα. Intestinal permeability of the common limb and colon was significantly improved in the RYGB group compared to the sham group. The mRNA levels of IL1β, IL6, and TLR4 in the intestine were significantly decreased in the RYGB group compared with the sham group. The expression levels of intestinal islet-derived 3β (REG3β), islet-derived 3γ (REG3γ) and intestinal alkaline phosphatase (IAP) were higher in the RYGB group than in the sham group. In conclusion, in a diet-induced obesity (DIO) mouse model, both decreased intestinal permeability and attenuated systemic inflammation after RYGB surgery were associated with improved innate immunity, which might result from enhanced production of IAP and antimicrobial peptides.